OPTIMIZING HOTEL DYNAMIC PRICES - A. M. Bandalouski; M. Y. Kovalyov (Informatika)
An approach to solvе a problem of determining optimal dynamic prices for hotel rooms is suggested. It includes selection of input parameters for the succeeding mathematical analysis, disaggregation of the demand into several categories, demand forecasting, simulation of demand- price relations, and a mathematical programming model for price optimization.